Evaluación de diferentes niveles de nitrógeno mediante la aplicación de briquetas de urea como alternativa para pequeños productores de arroz (oriza sativa), en la parroquia San juan, cantón pueblo viejo, provincia de los ríos. - Aguirre Coronel, David (2010)
This investigation focused on the "Evaluation of Different Levels of Nitrogen By applying briquettes of urea as Alternative for Small Farmers in Rice (Oryza sativa), which was determined with the productive effects, physiological and economic effects of th 14. The design was a design applied was completely randomized blocks with 5 treatments and 3 replications. The treatments were: T1: Witness dose as recommended by soil test with hectare of 50 kg). (1.66 kg). T2: urea briquettes in the dosages used by small farmers (2.06 bags of urea per hectare of 50 kg). (2.08 g). T3: urea briquettes in the dosages recommended by soil test (3.56 bags of hectare of 50kg). (3.6 g). T4: Urea briquettes T3 briquettes T3 +20% (4.29 bags of urea per hectare of 50kg). Statistical analysis were performed by ANOVA, Tukey and plant, batch production, and economic analysis. Using SPSS for the task. At the end of the study was obtained a greater effect fertilization T5.